Police-community relations crisis in our time - Earle, Howard H.; Pitchess, Peter J. (Charles C. Thomas, 1970)
Illustrated discussion of the need for constant attention to individual officers' conduct with members of the public, and methods to achieve positive experiences. Methods are discussed for developing support among various community groups, such as educational groups, advisory committees, juvenile groups, and the press. There are also sections on handling of civil disturbances and the various sociological problems that confront the police officer. The appendix contains the policy statement of the Los Angeles County Sheriff's Department and a code of ethics